Optical biosensors based on the surface plasmon resonance phenomenon: optimization of the metal layer parameters - Snopok, B.A.; Kostyukevich, K.V.; Lysenko, S.I.; Lytvyn, P.M.; Lytvyn, O.S.; Mamykin, S.V.; Zynyo, S.A.; Shepelyavyj, P.E.; Kostyukevich, S.A.; Shirshov, Yu.M.; Venger, E.F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
Application of the evanescent wave phenomena (e.g. surface plasmon resonance) in the chemical and biochemical sensors provides both optimal conditions for registration of specific interactions and high sensitivity. At the same time, the stability and reproducibility of parameters of a thin gold film (where the plasmon oscillations occur) are key problems for both (i) optimal transformation of biochemical information into the signal that is convenient for further treatment and (ii) the formation of artificial interfacial architectures. The paper presents results concerning the study of the deposition process temperature regimes influence on optical properties and structure of thin gold films. Morphological and topographic features of the thin film structures were analyzed using X-ray diffraction and atomic force microscopy, respectively. It is shown that the simple procedure of the low temperature annealing (at ~ 120°C) provides optimum parameters of thin gold films in view of their application as physical transducers in optical biosensors. Finally, the SPR transducer was fabricated with high sensitive elements used in the device «PLASMON-4M» elaborated in the Institute of Semiconductor Physics (NAS of Ukraine).